Understanding female gang involvement in Mitchells Plain, Western Cape: exploring female gang involvement - Vala, Nthabiseng (Department of Social Development, 2026)
The dissertation focuses on understanding female gang involvement in Mitchells Plain, Western Cape: Exploring Female Gang Involvement. The purpose of this study was to explore realities of female gang involvement in the Western Cape, South Africa in a township called Mitchells Plain making use of the Violentization Theory. Athens (1992) concept of ‘Violentization' was deemed suitable in order to explore how gangs are formed and to reflect on the lived experiences of female gangs. This qualitative study explores the experiences and perspectives of young females regarding gang involvement in Mitchells Plain town centre. Allowing a deep, detailed understanding of the participants' lives and the social dynamics influencing their decisions, particularly regarding gang involvement. Purposive sampling was utilized to identify and select 15 young females from Mitchells Plain who were relevant to the research topic. To ensure that the sample is particularly suited to provide the necessary insights and information about the gang involvement among young females. In this research, the sample consisted of 15 young females from Mitchells Plain. The sample size and composition are crucial as they impact the richness of the data collected and the depth of the analysis. By focusing on this specific group, the study aims to gather detailed and contextually relevant information about their experiences and perceptions. Semi-structured interviews were conducted face-to-face with the 15 young females. Allowing the researcher to gather consistent data across all interviews while also being adaptable to the unique experiences and insights each participant offers and facilitated a comprehensive understanding of complex issues. The results of this qualitative study indicated that although female gangs operate independently of male gangs, they remain subordinate to them and are often victimized and exploited. One significant factor contributing to young females joining gangs is adverse childhood experiences. The study's key findings revealed that many girls join gangs not only for safety and comfort but also as a means of employment. They are typically less suspected by law enforcement, which makes them valuable for processing and transporting drugs for both their male counterparts and themselves.